Botswana : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Botswana. (IMF Staff Country Reports; Country Report ;, 2010)
After several years of robust growth, real GDP growth slowed to 2.9 percent in 2008 owing to a decline in mining output. The nonmining primary deficit (NMPD) amounted to 28.6 percent of nonmining GDP in 2008/09, well above the 16.8 percent NMPD in 2007/08. Botswana continues to peg the pula to a basket of the rand and the SDR in an effort to maintain a stable real effective exchange rate (REER). The 12-month inflation rate fell to 8.4 percent in May 2009 from 15 percent in mid-2008, mostly reflecting reduced pressure on fuel and food prices.